Analisis Model Literasi Informasi Perguruan Tinggi Kota Malang Di Masa Pandemi COVID-19 - Dian Puspitasari; Melati Purba Bestari; Retno Widiyastuti Ika Wijaya (Media Pustakawan, 2021)
The study aims to analyze and evaluate the successful application of the information literacy model implemented during a pandemic. Information literacy models used include the Seven Pillars, The Big6TM and Empowering 8 and The Seven Faces of Information Literacy. The object of research is UPT Library of UMM, UB Library and UPT Library of UM. The research method used is descriptive research with a qualitative approach by conducting interviews. This study analyzed the comparison of the applied information literacy model and the use of the most effective information literacy models and programs in the UPT Library of UMM during the pandemic. The result of the research is that UPT Library of UMM has 3 packages of information literacy classes, and UB Library has a special literacy class which is held online during the pandemic. Meanwhile, the UPT Library of UM carry out literacy activities with individual / group guidance, casual literacy activities or informally at the library cafe. The conclusions show that during the COVID-19 pandemic the information literacy model applied in UMM Library upt and UB Library adopted The Big6TM theory. Information literacy had an impact on the ease of information management to complete scientific tasks and research. Meanwhile, UPT Library of UM is developing an information literacy model and providing information literacy through library cafes, reading wishes and search guidance. This activity has an impact on the ease of information retrieval for the completion of assignments and scientific papers. Inputs for the three libraries are adding literacy activities by providing space for creativity, holding information retrieval classes, and literacy competitions and being able to identify outputs/ products from information literacy.